1996
DOI: 10.1093/ptj/76.10.1097
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Ethical Issues in Physical Therapy Practice

Abstract: The 16 issues addressed ethical considerations in different areas of physical therapy practice: 6 issues involving patient rights and welfare, 5 professional issues, and 5 issues relating to business and economic factors. Thirteen of these issues have not been discussed in previous physical therapy literature and would be suggested topics for future study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 7 publications
1
23
0
5
Order By: Relevance
“…Through their scope-of-practice guidelines, many states have granted therapists autonomy of practice or role release to evaluate patients and/or initiate and provide therapy services without physician authorization. [55][56][57][58][59][60][61][62][63][64][65][66][67][68] However, it should be noted that state and federal regulations and third-party payers frequently mandate a physician's signature on prescriptions and treatment plans. If physicians sign off on prescriptions or plans without proper review or supervision, then they should be aware that they could be held legally responsible if adverse events, such as injuries, occur or if fraudulent practices, such as delivery of unauthorized or improper services, take place.…”
Section: Physician's Role In School-based Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through their scope-of-practice guidelines, many states have granted therapists autonomy of practice or role release to evaluate patients and/or initiate and provide therapy services without physician authorization. [55][56][57][58][59][60][61][62][63][64][65][66][67][68] However, it should be noted that state and federal regulations and third-party payers frequently mandate a physician's signature on prescriptions and treatment plans. If physicians sign off on prescriptions or plans without proper review or supervision, then they should be aware that they could be held legally responsible if adverse events, such as injuries, occur or if fraudulent practices, such as delivery of unauthorized or improper services, take place.…”
Section: Physician's Role In School-based Teamsmentioning
confidence: 99%
“…In the educational setting, therapists may be considered "service providers," a category that may include a number of NPHCPs. Articles on interdisciplinary teams produced by therapists [45][46][47][48][49][50][51][55][56][57][58][59][60][63][64][65][66][67][91][92][93][94][95][96] seem to recognize physicians as team members less frequently than those produced by physicians. 1,2, It has been suggested that physicians who assert their role in therapy and e620…”
Section: Physician's Role In Team Participationmentioning
confidence: 99%
“…[1][2][3] Physiotherapists are routinely involved in making ethically significant decisions, including those relating to service access and usage that emerge from stretched financial and human resources, heightened demand, and increased public expectations. [4][5][6][7] As the Canadian population ages, and life expectancy and the prevalence of chronic diseases increase, the need for physiotherapy will also grow. Faced with limited human and financial resources, publicly funded physiotherapy outpatient departments in Canada are required to prioritize patients for care.…”
mentioning
confidence: 99%
“…KEY WORDS: Bioethics; Ethics, professional; Physical therapy/education INTRODUÇÃO O desenvolvimento da Fisioterapia está associado à evolução de procedimentos e métodos de ensino-aprendizagem de conteúdos curriculares e aos avanços clínico-científicos da saú-de. Em decorrência dessa evolução, aumentou a expectativa por resultados positivos pós-tratamento e, também, a responsabilidade no ato de cuidar do paciente [1][2][3][4] . Exige-se do profissional, assim, uma formação generalista, humanista, crítica, reflexiva, autônoma, responsável e balizada em princípios éticos 5 .…”
unclassified
“…E à transformação do ato de cuidar, que atualmente enfatiza o vín-culo terapeuta-paciente 2,3,7 , mas carece de desenvoltura ética e moral 6,7 .…”
unclassified